THE EFFECTIVENESS OF USING SIMON SAYS GAME TO TEACH LISTENING - Murni, Rini Astuti; Zuhriyah, Mukminatus (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
The purpose of this study was to know the effectiveness of Simon says game on students’ listening ability at class VIII I of SMPN 1 Jombang. The method used in this research was quantitative method with a pre- experimental design. Population of the research was eighth grade of SMPN 1 Jombang, and the researcher used class VIII I as the sample of this research with total 30 students which consisted of 12 boys and 18 girls. The instrument of this study was listening test and it was conducted before (pre-test) and after (post- test) the treatment. The result of the data was analyzed using SPSS for windows ver.25. The mean score of students in the pre- test is 76,67 and the mean score of students in post- test is 95,17. Therefore, the paired sample t-test is 0,000 which is lower than 0,05. That means H0 is rejected (null hypothesis) and Ha is accepted (alternative hypothesis). To sum it up, the results show that Simon says game was effective on students’ listening ability. Keywords: effectiveness, listening ability, Simon says game